A case study on the effect of light and colors in the built environment on autistic children’s behavior - Nair, Ashwini Sunil; Priya, Radhakrishnan Shanthi; Rajagopal, Prashanthini; Pradeepa, Chandramouli; Senthil, Ramalingam; Dhanalakshmi, Samiappan; Lai, Khin Wee; Wu, Xiang; Zuo, Xiaowei (Frontiers in Psychiatry, 2022)
Background: The importance of strategies and services by caregivers and family members substantially impact the psychological and emotional well-being of autistic children. The rapid research developments in clinical and non-clinical methods benefit the features of autistic children. Among various internal and external factors, the influence of the built environment also impacts the characteristics of autistic children. This study investigates primarily the psychological effect of light and colors on the mood and behavior of autistic children to identify the most favorable and preferred indoor lights and color shades. Methods: A questionnaire survey was conducted at an autism center among autistic children and their parents. This study included autistic children aged between 6 and 16 (45 males, 42 females, mean age 8.7 years, standard deviation 2.3). Eighty-seven participants were involved in the survey to determine the sensory perceptions, intolerance, preferences, and sensitivities of children with an autism spectrum disorder towards colors and lighting. The margin of error at the statistical analysis's 95% confidence level is ±0.481. Results: As per this case report, the children have various color preferences and respond differently to different shades. Different hues have varying effects on autistic children, with many neutral tones and mellow shades proven to be autistic-friendly with their calming and soothing effect, while bright, bold, and intense colors are refreshing and stimulating. The stimulus of bright-lighting causes behavioral changes in autistic children prone to light sensitivity. Conclusions: The insights gained from this interaction with parents and caretakers of autistic children could be helpful for designers to incorporate specific autistic-friendly design elements that make productive interior spaces. A complete understanding of the effect of factors like color and lighting on the learning ability and engagement of autistic children in an indoor environment is essential for designers and clinicians. The main findings of this study could be helpful for a designer and clinicians to address designing an autism-friendly built environment with a color palette and lighting scheme conducive to their well-being and to maximize their cognitive functioning.